The Impact of the Ecranisation Process of the Novel Good Morning, Midnight (2016) into The Film The Midnight Sky (2020) - Shofiyanti, Farida; Dinanti, Putri Ayienda (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study was conducted to examine the ecranisation process of Lily Brooks-Dalton's novel Good Morning, Midnight into the film The Midnight Sky (2020). The analysis views the narrative changes and their impact on thematic meaning. To be specific, the purpose of this study is to identify the various forms of reduction, addition, and change in the adaptation, as well as to analyze the way these changes affect the representation of characters, redemption, and parenting relationships constructed in both mediums. This study employed qualitative method, and used the Eneste's concept of adaptation. The results have shown that the film adaptation is found to have an impact on the independence of the female characters, partly due to the removal of internal narration and detailed background information. As a result, the theme of redemption becomes less explicit, and the simplification of intergenerational relationships reduces the importance of parental identity in the overall meaning of the story. It can be concluded that the ecranisation process reveals the way adapting a literary work into film can redirect the thematic priorities and reshape the depth through which meaning is conveyed. Keywords:      Ecranisation, Film Adaptation, Novel to Film, Narrative Transformation, The Midnight Sky